The Role of OCB in Mediating Commitment, Motivation, and Performance of Teachers at SD Saraswati Denpasar - Komang Ayu Anggarani Trijati; I Ketut Setia Sapta; Agus Wahyudi Salasa Gama (International Journal of Economics and Management Sciences, 2025)
The purpose of this study is to investigate in depth the mediating role of Organizational Citizenship Behavior (OCB) in the relationship between organizational commitment and work motivation on teacher performance at Saraswati Elementary School, Denpasar. This research is motivated by the crucial role of teachers as the spearhead of educational success, making understanding the factors influencing teacher performance highly relevant. The study population comprised 175 teachers, with a sample size of 85 respondents determined using the Hair formula. Data collection involved a combination of structured questionnaires, in-depth interviews, and supporting document analysis to strengthen the findings. Path analysis was used to examine direct and indirect relationships between variables. The results indicate that organizational commitment has a positive and significant effect on OCB, indicating that the higher a teacher's commitment to the school, the greater their tendency to exhibit extra-role behavior. Similar findings were also evident for work motivation, where high motivation significantly increased OCB. Furthermore, organizational commitment was shown to have a direct, positive, and significant relationship with teacher performance, and work motivation also plays a significant role in improving performance. OCB itself also has a significant influence on strengthening teacher performance.  This study specifically confirms that OCB acts as a mediator in the relationship between organizational commitment and work motivation on teacher performance. Thus, the results of this study underscore the crucial role of OCB as a bridge connecting internal factors such as commitment and motivation with optimal work results. The practical implication of this research is the need for schools to strengthen organizational commitment and motivate teachers to develop citizenship behaviors that ultimately drive sustainable performance improvement.